2016
DOI: 10.1002/ejoc.201600037
|View full text |Cite
|
Sign up to set email alerts
|

Prevotella denticola Lipopolysaccharide from a Cystic Fibrosis Isolate Possesses a Unique Chemical Structure

Abstract: We report the first complete structural characterization of the lipopolysaccharide (LPS) from a cystic fibrosis (CF) clinical isolate of Prevotella denticola (B003V1S1X). Chemical, spectroscopic, and spectrometric analyses revealed a unique rough‐type LPS (LOS) structure. The structure has a highly negatively charged heptasaccharide core region containing hexoses, with the first two sugars, 3‐deoxy‐D‐manno‐oct‐2‐ulosonic acid (Kdo) and mannose, highly phosphorylated. Furthermore, the lipid A moiety has the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…In contrast, P. melaninogenica produced the greatest variety of short-chain fatty acids (associated with inflammation) amongst five tested anaerobes [18], and P. denticola shares similarities in its lipid A moieties to P. intermedia (a known pathogenic species), pointing towards pro-inflammatory traits [58]. Finally, certain strains of the periodontal disease-associated species, P. nigrescens, a close relative of P. intermedia, are thought to encode an enzymatic cell hydrolysis mechanism that destroys tissues.…”
Section: Resultsmentioning
confidence: 89%
“…In contrast, P. melaninogenica produced the greatest variety of short-chain fatty acids (associated with inflammation) amongst five tested anaerobes [18], and P. denticola shares similarities in its lipid A moieties to P. intermedia (a known pathogenic species), pointing towards pro-inflammatory traits [58]. Finally, certain strains of the periodontal disease-associated species, P. nigrescens, a close relative of P. intermedia, are thought to encode an enzymatic cell hydrolysis mechanism that destroys tissues.…”
Section: Resultsmentioning
confidence: 89%
“…For instance, P. melaninogenica, P. salivae , and P. nanceiensis may inhibit non-typeable Haemophilus influenzae -induced pro-inflammatory cytokine production by lung dendritic cells 52 , increased P. melaninogenica prevalence in CF airways has been associated with improved lung function 15 , and P. histicola can mute pro-inflammatory pathways triggered by P. aeruginosa in CF airways 55 . In contrast, P. melaninogenica produced the greatest variety of short-chain fatty acids (associated with inflammation) amongst five tested anaerobes 18 , and P. denticola shares similarities in its lipid A moieties to P. intermedia (a known pathogenic species), pointing towards pro-inflammatory traits 56 . Finally, certain strains of the periodontal disease-associated species, P. nigrescens , a close relative of P. intermedia , are thought to encode an enzymatic cell hydrolysis mechanism that destroys tissues.…”
Section: Resultsmentioning
confidence: 92%
“…The commensal and protective role of core throat bacteria found here and also in healthy subjects is still not elucidated; especially, the specific role of anaerobes in the lower airways remains controversial [ 30 ]. However, it was demonstrated that Prevotella and other anaerobes exhibit antimicrobial activities and a specific strain of Prevotella possessing an altered LPS had less immune-stimulatory activities [ 31 , 32 ]. Our data cannot exclude the hypothesis that CFTR mutation is modifying the niches and the regional growth for specific CF pathogens in the lungs and that those modifications are the driving force of the establishment of pathogens in the lungs.…”
Section: Discussionmentioning
confidence: 99%